Representations of Urban hood : The female characters in Shashi Deshpande’s Short Stories - Neetu Bissa Dr. Sarla Singla (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This research deals with the short stories of Shashi Deshpande, the prolific writer who through her works has consistantly been raising the questions related to women’s autonomy as an individual. Her stories deal with the plight of Indian middle class women, yet she talks about the challenges to be won, the tough time of decision making and efforts to achieve their aspirations. Being herself very ahead of time, Deshpande creates the female characters who are representatives of urban culture. In her short stories, there are only urban protagonists. This paper is an effort to put forth these protagonists urban traits and mentality which define their selfhood.